Democracy and governance networks: compatible or not? - Klijn, Erik-Hans; Skelcher, Chris (2007)
This paper investigates the relationship between representative democracy and governance networks at a theoretical level. It does so by offering four conjectures and their implications for theory and practice. The incompatibility conjectures rests on the primacy of politics and sees governance networks as a means of enabling greater participation in the policy process and sensitivity in programme implementation. The transitional conjecture posits a wider evolution of governance forms towards network relationships. The instrumental conjecture views governance networks as a powerful means through which dominant interests can achieve their goals. Illustrative implications for theory and practice are identified, inrelation to power in the policy process, the public interest, and the role of public managers. the heuristic potential of the conjectures is demonstrated through the identification of an outline research agenda. - Reproduced.
Keywords: Democracy; Public administration